Canadian Financial Accounting: Principles and Issues. (Book Review). - Meyer, Philip E.; Gibbins, Michael (The Accounting Review, 1981)
Reviews the book "Canadian Financial Accounting: Principles and Issues," by I.S. Rosen and M.H. Granof.